PERSEPSI MAHASISWA TERHADAP KUALITAS PELAYANAN REFERENSI DI UPT PERPUSTAKAAN UNPAD - Mulyani, Mulyani; Rohanda, Rohanda (Universitas Padjadjaran, 2015)
In this study, the authors wanted to determine and analyze the students perceptions about the quality of service in the reference section UPT Padjadjaran, namely: Tengible element Physical, Realibility reliability, Responsive Response, Assurance Guarantee, and Empathy attention. Meanwhile, the method used is exploratory, descriptive, and qualitative. The results showed that the hypothesis of the authors about the quality of service at the Library Unit Padjadjaran reference services there are still weaknesses evident. There are two drawbacks perceived by respondents as the visitors, namely: less complete collection and not humourist librarians in service to the visitors. It is expected to be input for the librarians at Padjadjaran University Library Unit that needs to be improved so that the quality of services librarians increased interest in reading them because they feel